Implementation of Integrated Quality Management Islamic Education in Madrasah Aliyah - Suriyati Suriyati; Bahaking Rama; Arifuddin Siraj; Muhammad Shabir U; St Syamsudduha (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
This study aims to analyze the implementation of integrated quality management of Islamic education at MAN 4, Bone Regency. This type of research is qualitative research with a descriptive design with a multidisciplinary approach, namely analyzing how integrated quality management of Islamic education is implemented. The several subjects in this study consisted of madrasa leaders, vice principals, educators, education staff, parents of students, and students. Data collection techniques are observation, interviews, and documentation. Data analysis was carried out interactively using the Miles and Huberman method which included data collection, data reduction, and drawing conclusions. The results of this research found that MAN 4 Bone Regency has implemented integrated quality management which includes a focus on customers, total involvement, measurement, commitment, and continuous improvement. The implementation of integrated quality management of Islamic education at MAN 4 Bone Regency has been running with reference to national education standards that are adjusted to the achievement targets on the vision and mission to be achieved by MAN 4 Bone Regency.